GE_GERICHTE P/1124/2012 vom 28. November 2012 - GE Cour de justice (2012)
; RENVOI(DROIT DES ÉTRANGERS) ; CONTRAINTE(DROIT PÉNAL) ; PROPORTIONNALITÉ | CPP.310; LUsC.2; LUsC.3; LUsC.9; LUsC.25; LETr.64; CP.14